Juridical Analysis of Polri's Role in Committing The Crime of Theft With Violenceabstrak - Juhrin Pasaribu (Badan Penerbit STIEPARI Press, 2023)
Whereas the legal arrangement for the role of the Indonesian National Police in tackling the crime of theft with violence is the Book of the Criminal Code Article 362 concerning Theft. Moreover, the mission by prioritizing changes in investigator behavior. Investigator behavior that must be changed immediately is a figure of power (arrogant). The factors that become obstacles to implementing accountability for the crime of theft with violence are the relevant statutory factors (legal substance), law enforcement factors, facilities or facilities, community factors, and cultural factors. Therefore, it is necessary to have legal arrangements to support the performance of police officers as law enforcers; there must be legislation that is burdensome for the perpetrators of the crime of theft accompanied by violence because this crime commits two criminal acts at the same time, so it has a powerful effect. For the victims, the enactment of burdensome legislation can provide a deterrent effect for perpetrators so that recidivism does not occur.